Global low-frequency motions in protein allostery: CAP as a model system - Townsend, P.D.; Rogers, T.L.; Pohl, E.; Wilson, M.R.; McLeish, T.C.B.; Cann, M.J. (Biophysical Reviews, 2015)
Allostery is a fundamental process by which ligand binding to a protein alters its activity at a distant site. There is considerable evidence that allosteric cooperativity can be communicated by the modulation of protein dynamics without conformational change. The Catabolite Activator Protein (CAP) of Escherichia coli is an important experimental exemplar for entropically driven allostery. Here we discuss recent experimentally supported theoretical analysis that highlights the role of global low-frequency dynamics in allostery in CAP and identify how allostery arises as a natural consequence of changes in global low-frequency protein fluctuations on ligand binding.
EPrint Processing Status: Full text deposited in DRO
Keywords: Protein; Allostery; Dynamics; Catabolite activator protein; Normal modes; Elastic network model